Memories of silk and straw : - Saga, Junichi (Kodansha International, 1987)
Contents: Preface Introduction, Around the town, Boatmen and fishermen, Shopkeepers and tradesmen, Women of the town, Geisha and Officers, Life in the countryside, Crafts and craftsmen, At school and at play.